If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 4x = 3 + -8x Solving 5 + 4x = 3 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 5 + 4x + 8x = 3 + -8x + 8x Combine like terms: 4x + 8x = 12x 5 + 12x = 3 + -8x + 8x Combine like terms: -8x + 8x = 0 5 + 12x = 3 + 0 5 + 12x = 3 Add '-5' to each side of the equation. 5 + -5 + 12x = 3 + -5 Combine like terms: 5 + -5 = 0 0 + 12x = 3 + -5 12x = 3 + -5 Combine like terms: 3 + -5 = -2 12x = -2 Divide each side by '12'. x = -0.1666666667 Simplifying x = -0.1666666667
| 30=6d | | 3x-8=2(2x+24) | | 15k-2=17 | | 3x+xy=9forx | | xdy-4(y+x^6)dx=0 | | 6.2n=310 | | x(5-x)=4.5 | | 0.95n=n+23 | | 0=8+3b | | 25-3x=2 | | 2/3n=7/9 | | -6+3x=x-6 | | 5(X+20)=7X+4 | | 7.50m+15=75 | | 4.56+y=2.5 | | 4w+4=4w+4 | | 5+1*7= | | 7-5x-2x=70 | | 2(x-50)^1/3=-10 | | 2(2y+3)=9y-15 | | 1/2(16) | | 5(8z+6)= | | y-(-1.5)=(8)*(x-2.5) | | 5/4=x7/7 | | 3n+13=-2n-12 | | 8x+5-5x=-2 | | 51=-3(4x-1) | | 5/4=x*7/7 | | 3(x-3)=5+2x+x | | 1/4d-3/4= | | 6m^1/4 | | 5k^3-15k^2=0 |